Investigating the Causes and Negative Effects of English Language Speaking Anxiety: A Case Study among EFL Learners at Kandahar University (American International Journal of Education and Linguistics Research, 2019)
The present study has been conducted to investigate the causes of English language speaking anxiety among EFL learners at Kandahar University. Furthermore, the second goal of the study to investigate the negative effects of speaking anxiety. This study uses a quantitative research approach. Similarly, the questionnaire had two parts the first part had comprised 14 items and the second part 7 items and applied randomly. Besides, the data analyzing was performed in SPSS (version, 24) and bring out the mean and standard division. Finally, the findings revealed those factors which caused EFL learners to feel anxiety during English speaking and numbered as follow: (1) I feel fear of making pronunciation mistakes, (2) I am afraid that my classmates will laugh at me when I speak English. (3) I feel worried during Performing communication orally. In addition, the following factors are the negative effects of anxiety on learners: (1) Anxiety limits my speaking fluency, (2) Anxiety causes me to become under pressure during presentation and (3) Anxiety decreases my oral performance and self-confidence.